2015
DOI: 10.5539/gjhs.v8n2p248
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Perceptions and Practices for Zambian Adults in Western Province at Risk for Hypertension: An Exploratory Descriptive Study

Abstract: Hypertension is an important public health issue in Zambia. Despite the need for early detection, treatment, and ongoing monitoring, there is little documented research on hypertension in Zambia. The study aims were to: 1) better understand risk factors for hypertension in urban and rural communities in Mongu and Limulunga Districts, Western Province; 2) identify current health practices for hypertension and prevention in these communities; and 3) explore intersections between culture and hypertension percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
7
14
2
Order By: Relevance
“…During the data collection for this study, we found that majority of rural participants said regular exercise was not a common practice because they viewed it as a part of their daily physical activity during working such as walking or farming. The participants' understanding regarding exercise and physical activity in this study was similar with a study by Oelke et al (2015) in Zambia. The benefit of exercise on sleep are still unclear, but may related to energy efficiency (Myllymaki et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…During the data collection for this study, we found that majority of rural participants said regular exercise was not a common practice because they viewed it as a part of their daily physical activity during working such as walking or farming. The participants' understanding regarding exercise and physical activity in this study was similar with a study by Oelke et al (2015) in Zambia. The benefit of exercise on sleep are still unclear, but may related to energy efficiency (Myllymaki et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…Four Health Checks in total were conducted; two in Mongu District and two in Limulunga District. Word-of-mouth recruitment strategies were used, based on their successful use in other recruitment efforts [ 13 ]. A sample size of 250, based on approximately 30 participants per variable, was deemed to provide sufficient power to detect significant relationships [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Zambia, studies of hypertension prevalence and risk factors have been sparse until more recently. Oelke et al [ 13 ] found a prevalence of 32.8% hypertension in Zambian adults living in Mongu, the urban capital of Western Province. Slightly lower prevalence rates have been reported in rural Zambia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population level data consistently show high salt consumption in SSA [9]. In Zambia for example, respondents in a survey always added salt to their food before eating and salt consumption was estimated to be twice higher than that recommended by the World Health Organization (WHO), even among hypertensive patients [10,11]. A reduction in dietary salt from the current intake of 10 grams per day to the recommended level of less than 5 grams per day, could have major bene ts for cardiovascular health with signi cant healthcare cost savings for both patients and the general population [5,12,13].…”
Section: Introductionmentioning
confidence: 99%